Sociological Structures and Accounting Misbehavior: An Institutional Anomie Theory Explanation of Restatements in Family Firms. Issue 2 (February 2023) - Mafrolla, Elisabetta; Matozza, Felice; D'Amico, Eugenio
This article studies the underinvestigated but fascinating issue of the sociological determinants of accounting misbehavior while focusing on an allegedly illicit accounting practice (i.e., restatement) in family- vs. nonfamily-controlled corporations. Under the framework of institutional anomie theory, we examined whether sociological structures (i.e., legal forces and cultural values) influence accounting errors inducing restatements. By applying a multivariate regression analysis to a sample of restating firms listed in 23 countries during the 2006 to 2014 period, we found that legal forces and cultural values significantly moderate the severity of accounting errors. The results of this study suggest that investors, managers, and policymakers should more fully consider the sociological structures of societies when debating the feasibility of corporate misbehaviors, as combining firm-level and country-level analyses could help to predict a firm's accounting misbehaviors, such as more severe accounting errors.